(untitled) (NPRC Journal of Multidisciplinary Research, 2025)
Background: Climate change impacts livelihoods worldwide, with agricultural communities being particularly vulnerable. The Tamang community in Tarebhir, Kathmandu Valley, provides a case study of how socio-economic and environmental factors interact with climate change to shape local livelihoods. Objective: This study investigates the perceptions of climate change and its effects on the livelihoods of the Tamang people. It explores how climatic and non-climatic factors influence agricultural practices, resource management, and socio-economic conditions. Methods: A mixed-methods approach is adopted by combining qualitative and quantitative data collection. In-depth interviews, focus groups, and field observations were conducted for 94 randomly selected household heads. The semi-structured questionnaire included both open and closed-ended questions. Primary data was supplemented with secondary data on the availability of rainfall and temperature records of the last 30 years drawn from the Department of Hydrology and Meteorology. Key themes were related to climate factors, cropping patterns, and socio-economic impacts. Results: The findings showed changes in sowing and harvesting dates, where the delay in maize and rice sowing was up to a month due to changed rainfall. A rise in temperature and deterioration in soil quality caused changes in crop maturation dates. The water resource at the local level had also deteriorated; the stream flow was reduced and the groundwater points had disappeared. The traditional resource use practices are supplemented by modern adaptations such as drought-resistant crops and the use of chemical pesticides, but with limited awareness of their implications on the environment. Modernization, population growth, and urbanization-which are socio-economic factors-cumulatively had a higher impact on livelihoods than climate change; however, this indirectly influenced economic activities through costlier agriculture, poor quality of agricultural produce, and health-related effects. Conclusion: Although relevantly indirect, the influence of climate change has been less imposing compared to socio-economic factors that have attacked the livelihood of the Tamang community. Some adaptations in agriculture, resource use, and economic strategies show resilience among the people. The findings bring forth the complex interrelationship of climate change with socio-economic dynamics in shaping rural livelihoods. Novelty: This study underlines the indirect influence of climate change on poor communities and integrates indigenous knowledge into current practices for sustainable adaptation. It also points out the compound effects of socio-economic changes, therefore providing insight into holistic challenges facing rural communities in rapidly urbanizing regions.